Folliculitis decalvans of the scalp - Gemmeke, Astrid (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Folliculitis decalvans of the scalp is a recurrent, purulent follicular inflammation leading to scarring alopecia. We report on a 27-year-old man withfolliculitis decalvans successfully treated with a combination of isotretinoin, corticosteroids, and clindamycin.
Keywords: Adult; Alopecia; Alopecija; Clindamycin; Drug Therapy; Folikulitis; Folliculitis; Isotretinoin; Izotretinoin; Klindamicin; Lasišče, dermatoze; Odrasli; Prednisolone; Prednizolon; Scalp Dermatoses